(untitled) (Journal of Universal Science Research, 2025)
This article examines ways to improve foreign language teaching in vocational education institutions using modern innovative approaches and their methodological foundations. Based on a literature review, the advantages of communicative, competency-based, interactive, and CLIL (Content and Language Integrated Learning) approaches are analyzed. The need to develop a foreign language teaching model in vocational education institutions that meets the professional needs of students is also substantiated.